Kinetic analysis of the reaction between electrogenerated superoxide and carbon dioxide in the room temperature ionic liquids 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and hexyltriethylammonium bis(trifluoromethylsulfonyl)imide - Buzzeo, M; Klymenko, O; Wadhawan, J; Hardacre, C; Seddon, K; Compton, R (2004)
The reduction of oxygen in the presence of carbon dioxide has been investigated by cyclic voltammetry at a gold microdisk electrode in the two room-temperature ionic liquids 1-ethyl-3-methylimidazolium bis- (trifluoromethylsulfonyl)imide ([EMIM][N(Tf)2]) and hexyltriethylammonium bis(trifluoromethylsulfonyl)imide ([N6222] [N(Tf)2]). With increasing levels of CO2, cyclic voltammetry shows an increase in the reductive wave and diminishing of the oxidative wave, indicating that the generated superoxide readily reacts with carbon dioxide, The kinetics of this reaction are investigated in both ionic liquids. The reaction was found to proceed via a DISP1 type mechanism in [EMIM][N(Tf)2], with an overall second-order rate constant of 1.4 ± 0.4 × 103 M-1 s-1. An ECE or DISP1 mechanism was determined to be the most likely pathway for the reaction in [N6222][N(Tf)2], with an overall second-order rate constant of 1.72 ± 0.45 × 103 M-1 s -1.